PERANCANGAN JARINGAN DENGAN PROTOKOL EIGRP DI UNIVERSITAS UDAYANA - Vidananda Agastya, Ida Bagus; Wiharta, Dewa Made; Putra Sastra, Nyoman (Jurnal SPEKTRUM, 2021)
In this journal, a new network is designed in the area of Udayana University, Bukit Jimbaran Campus using Cisco Packet Tracer. The purpose of this design is to build a network that can improve efficiency in the process of exchanging data and information. The design uses one dynamic routing, namely Enhanced Interior Gateway Routing Protocol (EIGRP). EIGRP was chosen because this protocol is the only protocol that has a backup system. In addition, the network that is designed also uses a ring topology, with the consideration that the ring topology is the best topology for building networks with service areas in the form of rotations. Analysis of the designed network performance has been carried out by sending PING with several scenarios to obtain packet loss, throughput, and delay parameter values. Based on the research results obtained the same packet loss parameter value for each case that is 0%, the average value of throughput is 4,398 bps, and the average delay value is 10.125 ms. The three results of each of these parameters meet the requirements of the TIPHON in the excellent category and have a class 4 index.